Oil Price Changes and the Libyan Economy: Perceptions of Libyan Experts - Elsharif, Idris Elsharif (Dirasat in Economics and Business, 2005)
The impact of oil price changes on the demand for (and the supply of) the output of the oil and gas industry suggests that increased knowledge about the nature and effect of crude oil price movements is likely to be of interest to most institutions and organisations in the global econ omy. The importance of the energy sector is evident even in country as Libya where the nation's massive dependence on oil export revenues renders the economy especially prone to significant swings in oil prices. to reduce their impact; and (111) the role of UN and US oil sanctions on the Libyan econo my. The more general aim of the paper is to examine the extent to which perceptions regarding oil price change exposure in a developing country without a liquid stock market but with a great dependence on the success of the oil industry